Islamic Education and Family Mental Health: A Model of Development of Mental Disorders Patients through a Religious Approach in Paringan Ponorogo - Mahmudin, Afif Syaiful (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
In 2011, the residents of Ponorogo were taken aback by the sudden appearance of “Kampung Gila” in Paringan Jenangan Ponorogo village, where 60 individuals were identified as suffering from mental disorders. A survey conducted by the Malang Mental Hospital and the Ponorogo Regional Government revealed that a significant proportion of individuals diagnosed with schizophrenia experienced discrimination, including being confined by their families and communities. Despite the long-standing nature of this issue, it was not addressed with any urgency. One strategy to address mental health issues in Paringan was based on a religious framework. This approach integrates medical treatment with Islamic religious education, with the objective of providing patients with guidance from both familial and religious sources. Parents, with varying degrees of religious comprehension and disparate parenting styles, assume a pivotal role in the coaching process. The results of this guidance have been favourable, with patients displaying increased independence, emotional stability and social sensitivity. Furthermore, they are able to engage in worship with greater regularity and dedication, and to live more productive and fulfilling lives without causing harm to their families or to the wider community.